2022
DOI: 10.3389/fpsyg.2022.1011285
|View full text |Cite
|
Sign up to set email alerts
|

Falls efficacy: The self-efficacy concept for falls prevention and management

Abstract: November CITATION Soh SLH () Falls e cacy: The self-e cacy concept for falls prevention and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The MFES is a highly validated fear of falling assessment tool 4) . Previous studies of hospitalized older adult participants have reported that the lower the score 2) , the higher the likelihood of falling 7) . However, the characteristics of fear of falling that are associated with falls have not been clarified to date.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The MFES is a highly validated fear of falling assessment tool 4) . Previous studies of hospitalized older adult participants have reported that the lower the score 2) , the higher the likelihood of falling 7) . However, the characteristics of fear of falling that are associated with falls have not been clarified to date.…”
Section: Introductionmentioning
confidence: 93%
“…The Modified Falls Efficacy Scale (MFES) 2) is commonly used to assess the fear of falling. The MFES is a highly validated fear of falling assessment tool 4) .…”
Section: Introductionmentioning
confidence: 99%
“…4 A recent study has concluded that falls efficacy is a wide concept that involves perceived ability to prevent and manage falls, and that applying measures for the targeted construct is helpful for the perceived capability in preventing and managing falls. 5 Users of lower limb prostheses often experience more falls and have a heightened fear of falling, with most prosthesis users reported having fallen at least once in the past year. 6,7 In another study, just over half of the participants reported having fallen in the past year, while just below half reported fear of falling.…”
Section: Introductionmentioning
confidence: 99%
“…4 A recent study has concluded that falls efficacy is a wide concept that involves perceived ability to prevent and manage falls, and that applying measures for the targeted construct is helpful for the perceived capability in preventing and managing falls. 5…”
Section: Introductionmentioning
confidence: 99%
“…Falls are a serious concern in older adults as they can result in injuries such as fractures, head trauma, or even fatality (Iamtrakul et al, 2021;Rubenstein, 2006) even more during (Jung et al, 2023) and after COVID-19 (Briguglio et al, 2020). Therefore, it is crucial to identify and address potential fall risks to prevent injuries or fatalities (Soh, 2022). The fear of falling is a common concern among older adults, characterized by a heightened sense of apprehension regarding falls and their consequences (Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%